IDEOLOGY OF COMMODIFICATION OF BARONG PERFORMING ART AT BANJAR DENJALAN-BATUR, BATUBULAN, GIANYAR - Subrata, I Wayan (E-Journal of Cultural Studies; Volume 7, Number 3, Agustus 2014, 2014)
Performing arts barong in Banjar Denjalan - Batur Batubulan Gianyar is one tourist attraction that deliberately conceived , produced , and distributed to the travel agency for domestic consumption and foreign tourists . The ideology behind the commodification of performing arts barong able to make it existed until now to meet the needs of tourism in Bali . This paper mengangakat problem of ideology whether contained in the commodification of performing arts in Banjar Denjalan barong - Batur Batubulan Gianyar Bali that can be accepted by the community and be a tourist attraction . Research using observation , interviews , and documentation . In summary this study was described as follows . Ideology balih - balihan ( art entertainment commercial nature ) that underlies the commodification of performance art barong by making a duplicate original as the original but not profane staged regularly every day at two venues , the stage and the stage Pura Pura Pererepan Puseh . The original performing arts barong ( sacred ) staged in terms of religious ceremonies in temples called bebali art . Behind it all has the objective to obtain pecuniary advantage . Income of performing arts barong for subsistence for the owners of the performing arts barong and local communities and stakeholders .
Keywords: ideology; commodification; barong performing arts; bebali; balih - balihan